Experimental Investigation on Emission Characteristics of a Marine Diesel Engine with Catalytic Convertor for Compliance with Marpol Regulations - Sundara Raman, R.; Sankaranarayanan, G.; Manoharan, N.; Sendilvelan, S. (Asian Review of Mechanical Engineering, 2015)
In this paper, the study of methods to minimise SOx , NOx and particulate matter is done using a catalytic convertor. The dilution has been done for the emissions from an compression ignition engine i.e, a diesel engine . The validation of the diluted emissions gives a clear picture that the catalytic converter used is in compliance with the MARPOL Regulations . All the necessary equipment is a replica of a compression ignition engine that may be used onboard a ship and the fuel used in this engine is the similar fuel that is used onboard a ship for a diesel engine. The validation has been carried out in two different stages i.e, first for the emissions before dilution and second after the dilution and hence the results are compared to show the effectiveness of the current catalytic convertor.